Peningkatan Kompetensi Dosen Pembimbing Klinis Dalam Menyusun Soal OSCE (Objective Structered Clinical Examination) - Surya Akbar; Tezar Samekto Darungan; Halimah Tania (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
This community service is taken in training form. Training is given to clinical supervisors with the aim of increasing the competence of clinical supervisors for evaluating achivement of clerkship in clinical learning process. The training used a four steps method, i.e: namely: determining the level of competence, compiling disease case scenarios, entering disease case scenarios into the OSCE template, completing information related to OSCE and assessment rubric. Using this method, clinical supervisors are proven to be better at composing OSCE questions. The results of this training, there is 7 OSCE questions had made from 7 departments. A review of these questions resulted in two questions that did not match between the level of assessment with the level of competence; one question that has excess time allocation and 2 questions that have less time allocation. In the future, the preparation of OSCE questions must be carried out routinely by clinical supervisors, so that clinical supervisors are used to preparing OSCE questions. The questions collected need to be revised so that they can be used in the OSCE exam.